Volcanic Lateral Collapse Processes in Mafic Arc Edifices: A Review of Their Driving Processes, Types and Consequences - Romero, Jorge E.; Polacci, Margherita; Watt, Sebastian; Kitamura, Shigeru; Tormey, Daniel; Sielfeld, Gerd; Arzilli, Fabio; La Spina, Giuseppe; Franco, Luis; Burton, Mike; Polanco, Edmundo (Frontiers in Earth Science, 2021)
Volcanic cones are frequently near their gravitational stability limit, which can lead to lateral collapse of the edifice, causing extensive environmental impact, property damage and loss of life. Structural failure of edifices is related to a number of factors relating to edifice growth, erosion, gravitational spreading and hydrothermal alteration. As such, more mature, larger, and morphologically complex edifices may be considered prone to structural failure, and yet it is clear that collapses occur across all volcano types and in all tectonic settings, including in relatively small, morphologically youthful edifices. Here, we examine collapses in these relatively structurally simple volcanoes, often erupting a narrow compositional range, which we broadly term mafic volcanoes. This still encompasses a broad range of volcano dimensions, but the magma types erupted in these systems represents the most abundant type of volcanism on Earth and rocky planets. Their often high magma output rates can result in rapid construction of gravitationally unstable edifices susceptible both to small landslides but also to much larger-scale catastrophic lateral collapses. Although recent studies of basaltic shield volcanoes provide insights on the largest subaerial lateral collapses on Earth, the occurrence of lateral collapses in mafic arc volcanoes lacks a systematic description, and the features that make such structures susceptible to failure has not been treated in depth. In this review, we address whether distinct characteristics lead to the failure of mafic arc volcanoes, or whether their propensity to collapse is no different to failures in volcanoes dominated by intermediate (i.e. andesitic-dacitic) or silicic (i.e. rhyolitic) compositions? We provide a general review on the stability of mafic arc edifices, their potential for lateral collapse, and the overall impact of large-scale sector collapse processes on the development of mafic magmatic systems, eruptive style and the surrounding landscape. Through a global review of lateral collapses in mafic arc volcanoes, we develop a comprehensive classification of their occurrence and highlight perspectives for future research.